Optimization of laser melting parameter to enhanced surface properties in hot press forming die - Norhafzan, B.; Aqida, S. N.; Khairil, C. M. (IOP Publishing, 2021)
This paper presents laser melting process with various parameter to enhanced surface properties of AISI H13 tool steel. The design of experiment (DOE) optimisation was conducted to obtain significant model using regression analysis. DOE were analysed using response surface method (RSM) with Box-Behnken design approach. Design Expert 7 software was used to design parameter of laser melting process. The laser melting processes was conducted using Nd:YAG laser system with pulsed mode at a constant average power of 100 W, overlapping rate of 30 to 50%, peak power of 1700 to 2500 W and pulse repetition frequency (PRF) of 50 to 70 Hz respectively. The responses were characterised for sub-surface hardness, melt depth and surface roughness. The results show that optimum parameter of 2500 W peak power, 60 Hz PRF and 30% overlapping rate produced highest surface hardness of 793.7 HV0.1 with 0.21 mm melted depth and 3.89 µm surface roughness from experimental data. This finding was important to enhance properties of AISI H13 tool steel for hot press forming die using laser process.